Utilization of wearable smartwatch and its application among Saudi population - Alaskari, Entesar; Alanzi, Turki; Alrayes, Saja; Aljabri, Duaa; Almulla, Salma; Alsalman, Demah; Algumzi, Areej; Alameri, Rana; Alakrawi, Zahraa; Alnaim, Norah; Almusfar, Latifa; Alotaibi, Leyan; et al. (Frontiers in Computer Science, 2022)
Study purpose: the objective of this study was to understand the actual consumers' perceptions of towards the use of smartwatches and explore the critical factors affecting the adoption and intention to use smartwatches in the Kingdom of Saudi Arabia. Methods: A cross-sectional study was designed to assess the actual perception of use smartwatches and to investigate the influencing factors that affect the utilization among Saudi population using the survey technique. Questionnaire design was based on the domains of Technology Acceptance Model (TAM) to determine the factors affecting smartwatches utilization. The sample composed of Saudi Arabian residents aged 18 years and above. The response rate for the online questionnaire that was distributed through the social media applications was 58.61% representing 135 participants. The data was collected in November 2020 and analyzed using the Statistical Packages for Software Sciences (SPSS). Results: This study included 135 respondents to evaluate their use of wearable devices (smart watch). The most common age group was 35 – 44 years (40.7%) with more than a half (55.6%) were males, 46.7% were bachelor’s degree holders, and nearly two third (65.9%) were employed with 40.7% of them earned 10,001 – 20,000 SAR per month. The prevalence of participants who had knowledge about smartwatch was 94.1%. When comparing the demographic characteristics between those owning and not owning a smartwatch, it was found that educational level (X2=9.365; p=0.025) and knowledge about smartwatch (X2=7.897; p=0.005) had significant relationship with owning a smartwatch. When comparing between design aesthetic, perceived usefulness, ease of use, enjoyment and healthology in relation to the socio demographic characteristics, it was found that respondents in the older age group (≥45 years) (F=11.797; p<0.001) and those with master degree (F=3.449; p=0.002) observed to have significantly lower mean score in design aesthetic while females exhibited significantly higher score in perceived enjoyment and healthology (T=-3.629; p=0.001) as well as design aesthetic (T=-2.070; p=0.043). Conclusion: Factors such as age, education, gender, income can significantly affect the adoption of wearable devices in Saudi Arabia